Recognizing Innate Transformational Traits in Public Administrative Services: Are We Doing Right?. Issue 7 (18th May 2020) - Marathe, Gaurav; Kakani, Ram Kumar
ABSTRACT: With shifting paradigm, public administration needs even more transformational leaders. A large part of an individual's leadership potential refers to innate personality traits which are brought out by relevant nurturing processes. Environment, favorable or unfavorable, interacts with these processes and impacts the flourishing of natural potential. Experience promotes the positive growth of innate potential that one possesses. Using data from India, this article looks into the systematic impact of public administrative training institutes on the development of top-tier civil servants. By comparing the performance of officers in public administration training academy possessing innate personality traits suitable for transformational leadership vis-à-vis innate personality traits suitable for transactional leadership, we test whether current training evaluation promotes transformational innate personality traits and suggests the implications. Interestingly, our mix-method study evaluating the entry-level induction training of public administrative leaders reveals that there is a gap between theory and praxis.